The impact of the maritime labour convention on shipowners' practices - Ng, Douglas Yong Kang (2017)
Seafarers play an important role in today’s economy due to the dominance of shipping in the world trade, as 90% of the world trade volumes are transported by sea. They are subjected to conditions out at sea that push both physical and mental limits due to the at sea and isolation from their loved ones for months at a stretch. Thus, in the face of such a working environment, it is of utmost importance to ensure that regulation is needed to safeguard their welfare and wellbeing. As a result, the Maritime Labour Convention (MLC) was introduced by the International Labour Organization (ILO) in 2006, and was implemented in 2013 after meeting the minimum number of ratifications by ILO member states. Throughout the 4 years of implementation, the impact of the convention can be felt by many stakeholders throughout the shipping industry, ranging from ship-owners, maritime authorities, seafarers to crewing agencies who will have to respond to changes set by MLC. Therefore, this project aims to identify the changes made by different stakeholders in accordance to MLC, and whether the convention is beneficial to them. To do so, a qualitative approach is used, tapping on experiences and knowledge from industry leaders to determine the actual impact the Convention has had on their daily operations. This paper focuses from the perspectives of shipowning companies and individual shipowners. Based on the information gathered, the key issues regarding MLC implementation were mainly Seafarers’ Employment Agreements (SEAs), seafarers’ wages and the provision of recreational facilities. The root of these issues stems from the practical situation onboard vessels and the existing practices companies were practising before MLC.